(RE)THINKING SEXUAL ACCESS FOR ADOLESCENTS WITH DISABILITIES IN SOUTH AFRICA: BALANCING RIGHTS AND PROTECTION (African Disability Rights Yearbook, 2021)
The subject of sexual rights and disability is a largely underdeveloped sphere in relation to African rights discourse. This subject becomes even more contested and unacceptable when discussing access in relation to sexual expression or relationships amongst adolescents with disabilities. Most commonly, adolescents with disabilities are often denied their sexual autonomy and are generally depicted as being non-sexual and incapable of sexual agency. In view of this, while adolescents with disabilities continue to gain recognition as citizens with the same equal opportunities as their non-disabled peers, they have not as yet truly emerged as sexual citizens within the African context. This article aims to (re)position discourses of sexual access in relation to adolescents with disabilities in South Africa. In particular, the article outlines the importance of supporting and nurturing the sexual autonomy of adolescents with disabilities. The article also outlines the way in which international rights conventions and national legislation may impact sexual encounters amongst adolescents with disabilities and what this means for significant adults working with adolescents with disabilities.
Keywords: sexual rights; disability; adolescents; sexual autonomy; international rights conventions; national legislation